2005
DOI: 10.1111/j.1365-2869.2005.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective fatigue and subjective sleepiness: two independent consequences of sleep disorders?

Abstract: SUMMAR Y The objective of this investigation was to evaluate subjective fatigue versus subjective sleepiness as independent consequences of sleep disorders. Furthermore, we tried to explore how these symptoms relate to alertness, depressive symptoms and illness intrusiveness. In a prospective observational study, 283 sleep-disordered patients referred to a hospital-based sleep laboratory for various indications over a 1-year period were evaluated vis-a`-vis fatigue and sleepiness. All patients completed five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
1
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(178 citation statements)
references
References 56 publications
12
151
1
10
Order By: Relevance
“…19 EDS may also account for impaired cognitive performance in cerebellar ataxia as it has been shown to negatively impact cognitive domains such as attention, memory, motivation and alertness, thus affecting mood, productivity, and quality of life. [20][21][22][23][24] We have also demonstrated that emotional reactivity is maintained by sleep. 25 This role of sleep in emotional processing may contribute to mood regulation.…”
Section: The Effects Of Sleep Dysfunction On Cognition Affect and Qmentioning
confidence: 81%
“…19 EDS may also account for impaired cognitive performance in cerebellar ataxia as it has been shown to negatively impact cognitive domains such as attention, memory, motivation and alertness, thus affecting mood, productivity, and quality of life. [20][21][22][23][24] We have also demonstrated that emotional reactivity is maintained by sleep. 25 This role of sleep in emotional processing may contribute to mood regulation.…”
Section: The Effects Of Sleep Dysfunction On Cognition Affect and Qmentioning
confidence: 81%
“…It is not clear to what extent such observations can be generalized to long-term sickness absence per se. However, sleep and fatigue often correlate highly in cross-sectional studies 23,24) and reduced sleep duration involves gradual accumulation of sleepiness/fatigue 25) .…”
Section: Discussionmentioning
confidence: 99%
“…Although insomnia is typically associated with nighttime pathology, a particularly prominent complaint is the resultant daytime fatigue. 16 This daytime pathology, characterized by fatigue, cognitive complaints and low mood, can interfere with daily functioning. Thinking repeatedly about what caused daytime symptoms such as fatigue and poor concentration, can reinforce beliefs of poor sleep self-efficacy, increase anxiety about solving one's sleep problem, and may lead to maladaptive safety behaviors (e.g., spending more time in bed).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%